Kohezivno-konektorska sredstva v besedilih, nastalih v predvolilnih obdobjih - Krajnc Ivič, Mira (Slavistična revija, 2015)
According to semiotics, a text is a complex linguistic sign examined from semantic, syntactic, and pragmatic points of view. The latter includes the language user, as (s)he is the only one to whom the signifier evokes the signified and vice versa. This should also be taken into consideration in the analysis of cohesive-connective language devices as simple signs that structure a text and show vibrations of language with time, space, and man.
Keywords: besedilnost; besedilo; cohesion; connectivity; discourse; diskurz; kohezivnost; koneksija; predvolilna obdobja; Slovene; Slovene language; slovenščina; text; textuality